Media Sosial Sebagai Sarana Dakwah : Perspektif Keislaman dan Peralihan dari Masa ke Masa - Hanna Nurul Khoirunnisa; Najwa Azahra; Putri Sheila Az Zahra3; Rahma Dhita Syakirah; Sandi Novaeldi Rhamadan; Subur Herdiana; Rika Widawati (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Technological progress is concrete evidence in life in the modern era. Its urgency has spread widely to various fields. One of them is social media. Social media is one source of information used by the wider community. Nowadays, social media is considered a necessity in life. It cannot be denied that the function of social media is used as a form of convenience in providing or obtaining information covering several aspects, especially in the religious field. Islam utilizes the existence of social media as a means of da'wah. to facilitate and expand regional coverage in accepting Islamic teachings. The research method used is a qualitative method with a library research approach based on previous research. The results of this research state that all ulama agree with the use of social media as a means of da'wah by paying attention to the ethics and norms of using social media. This is believed to be a form of spreading Islamic teachings so that the messages conveyed spread easily. The transition from time to time in conveying da'wah certainly uses different methods. It is hoped that social media will play a role as a means of developing the da'wah methods carried out from the time of the Prophet Muhammad SAW until now. So that the urgency of preaching can be conveyed perfectly. From this research, it is hoped that all Muslims can use social media well as a means of da'wah to spread Islamic teachings to a wider scope so that we can apply its essence in everyday life.